THE ADDITION OF BANANA BUD (Musa paradisiaca normalis) IN THE FLOSS FISH OF CAT FISH (Clarias gariepinus) - Yefri Mufti; N. Ira Sari; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was aimed to evaluate the effect of banana budsuplementation to the quality of shredded catfish (Clarias gariepinus). The methodused was experimental, composed as non factorialcompletely randomized design (CRD).The treatment was the addition of banana bud into the shredded catfish, whichwas varied at 4 levels, namely: 0 % or original shredded catfish as the control(A0), addition of banana bud 25% (A1), 50% (A2) and 75% (A3) for 10 tones fishmeat each. The parameters used were organoleptic evaluation and proximatecomposition. The result showed that the addition of banana bud 75% (A3) into thefish meat was producing the best shredded catfish, characterized by the goodappearance with the brown-grey colour; have special good taste of shredded fish;fluffy fiber, soft and dry textured; and more tasty flavor. The product contained6,89% moisture, 26,25% protein, 27,19% fat, 6,31% ash, and 2,57% fiber.Keyword: banana bud, catfish, shredded fish,